Functional Outcome on Surgical Treatment For Lower Extrimity Tuberculosis Arthritis At Cipto Mangunkusumo Hospital Jakarta - Mirna Phandu; Ismail HD (Medicinus, 2020)
Introduction: Osteoarticular tuberculosis more frequently occur on weight bearing joints.1,8 On late stage tuberculosis osteoarthritis choices of surgical treatment involved synovectomy, osteotomy, arthrodesis, and arthroplasy11 Results on functional outcome after surgery would be useful to decide appropriate treatments and prognosis.Method: This descriptive analytic study involved all lower extremity tuberculosis osteoarthritis that underwent surgical procedure at Cipto Mangunkusumo hospital in 5 years periods from 2008 to 2012. Follow up performed for minimal 6 months after surgery. Patients were evaluated using Lower Extremity Functional Score (LFES) and functional score according the joints involved, including Harris Hip Score (HHS), Knee Society Score (KSS), and Foot & Ankle Disability Index (FADI). Results: Study only involved late stage cases with average age at surgery was 30.04 (SD 16,67) years old. Average follow-up 33.68 months (SD 18.67). There are significant difference (p<0.001) of the LFES between preoperative (27.41), 6 months after surgery (42.19) and on last follow up (63.04). There were also difference (p<0.001) on Functional Score (HHS, KSS and FADI) preoperative (27.48), 6 months after surgery (60.11) and on last follow up (82.56). There is positive correlation between time of follow up and LEFS on last follow up. On last follow up, there is also significant difference of LEFS between groups that had arthrodesis and arthroplasty (p 0.045.)Conclusions: Results of surgical treatment gave significant improvement on functional outcome of the joint involved.  The result however is correlated to the type of joints involved, type of surgery performed and the time after surgery.